Native to the nation : disciplining landscapes and bodies in Australia - Cerwonka, Allaine (Borderlines (Minneapolis, Minn.), 2004)
Focusing on Australia, Allaine Cerwonka examines the physical and narrative spatial practices by which people reclaim territory in the wake of postcolonial claims to land by indigenous people and new immigration of "foreigners."Native to the Nation provides a multisited ethnography of two communities in Melbourne, allowing us to see how bodies are managed and nations physically constructed in everyday confrontations.